ALTERNATIF PEMBIAYAAN LEASING DAN DEBT FINANCING AKTIVA TETAP PADA UD. RIKY S.Y DI DESA GONTORAN KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - EKA PERMADI, I GUSTI AGUNG DIDIT (Universitas Mahasaraswati Mataram, 2019)
The progress activity of aquaculture which conducted by UD. Riky S.Y have got the increase since 2008, so that the company make plan to expand their bussiness, they need a number of fixed asset such as pool of pisciculture and car, to overcome the problem there are two alternatives of aquasition financing fixed asset is applied. First alternative applied is leasing and for to second alternatives by using debt financing, kind of this research is applied research by case study method, and data received by applying data collecting tehknique, namely observation, interview, and documentation, to answer the question proposed in this research is analysis of present value, by criteria choice that is present value which has the smaller financing. From analysis data and discussion received that present value of spent cash flow for pool pisciculture by measuring is 16 x 6m with leasing alternative of period for 2013/2014 – 2017/2018 is about Rp 48.278.250 while for debt financing alternative for the same period is about Rp 66.530.066, spent cash flow for car by leasing alternative for the same period is about Rp398.823.300, and for debt financing alternative is about Rp 222.446.799 and can be recommended to UD. Riky S.Y to apply the leasing alternative and debt financing alternative in receiving the fixed asset